Graffiti Scratched, Scrawled, Sprayed (De Gruyter, 2024)
Over the last two decades, the study of graffiti has emerged as a bustling field, invigorated by increased appreciation for their historical, linguistic, sociological, and anthropological value and propelled by ambitious documentation projects. The growing understanding of graffiti as a perennial, universal phenomenon is spurring holistic consideration of this mode of graphic expression across time and space. Graffiti Scratched, Scrawled, Sprayed: Towards a Cross-Cultural Understanding complements recent efforts to showcase the diversity in creation, reception, and curation of graffiti around the globe, throughout history and up to the present day. reflecting on methodology, concepts, and terminology as well as spatial, social, and historical contexts of graffiti, the book’s fourteen chapters cover ancient Egypt, Rome, Northern Arabia, Persia, India, and the Maya; medieval Eastern Mediterranean, Turfan, and Dunhuang; and contemporary Tanzania, Brazil, China, and Germany. As a whole, the collection provides a comprehensive toolkit for newcomers to the field of graffiti studies and appeals to specialists interested in viewing these materials in a cross-cultural perspective. ; Over the last two decades, the study of graffiti has emerged as a bustling field, invigorated by increased appreciation for their historical, linguistic, sociological, and anthropological value and propelled by ambitious documentation projects. The growing understanding of graffiti as a perennial, universal phenomenon is spurring holistic consideration of this mode of graphic expression across time and space. Graffiti Scratched, Scrawled, Sprayed: Towards a Cross-Cultural Understanding complements recent efforts to showcase the diversity in creation, reception, and curation of graffiti around the globe, throughout history and up to the present day. reflecting on methodology, concepts, and terminology as well as spatial, social, and historical contexts of graffiti, the book’s fourteen chapters cover ancient Egypt, Rome, Northern Arabia, Persia, India, and the Maya; medieval Eastern Mediterranean, Turfan, and Dunhuang; and contemporary Tanzania, Brazil, China, and Germany. As a whole, the collection provides a comprehensive toolkit for newcomers to the field of graffiti studies and appeals to specialists interested in viewing these materials in a cross-cultural perspective.